Occurrence of Atta laevigata (Hymenoptera: Formicidae) in the South of Espírito Santo State, Brazil. Recently introduced or endangered species? - Zanuncio, Antônio José Vinha; Zanuncio, José Cola; Mayhé-Nunes, Antônio; Zanetti, Ronald; Polanczyk, Ricardo Antonio [UNESP]; Serrão, José Eduardo (My University, 2010)
Ants of the genus Atta are the main pests of Brazilian agriculture, including annual crops, pasture and reforestation. Atta laevigata (F. Smith) (Hymenoptera: Formicidae) presents a wide distribution from the Northern Amazon Basin Region to Southern Brazil. However, this is the first report of its occurrence in the Espirito Santo State, Brazil where it was found in the Municipality of Castelo at 20° 36'13 South Latitude, 41° 11'05 West Longitude and an average altitude of 100 meters. The low number of nests of A. laevigata compared to those of Atta sexdens rubropilosa Forel may indicate that the first species has been recently introduced or is endangered in Espírito Santo State due to competition with other organisms or by the impact of anthropogenic factors.
Keywords: Atta laevigata; Leaf-cutting ants